Voltage disturbance mitigation in Iraq's low voltage distribution system - Jamal Abdul-Kareem Mohammed; Arkan Ahmed Hussein; sahar R. Al-Sakini (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Power distribution network in Iraq still suffers from significant problems regarding electricity distribution level. The most important problem is the disturbances that are occurring on lines voltages, which in turn, will negatively affect sensitive loads they feed on. Protection of these loads could be achieved efficiently and economically using the dynamic voltage restorer DVR when installed between the voltage source and load to inject required compensation voltage to the network during the disturbances period. The DVR mitigates these disturbances via restoring the load voltage to a pre-fault value within a few milliseconds. To control the DVR work, dq0 transformation concept and PID method with sinusoidal pulse-width modulation SPWM based converter had been used to correct the disturbances and thus enhance the power quality of the distribution network. The DVR performance was tested by MATLAB/Simulink with all kinds of expected voltage disturbances and results investigated the effectiveness of the proposed method.